2016
DOI: 10.1007/978-3-319-47437-3_45
|View full text |Cite
|
Sign up to set email alerts
|

One-Shot Evaluation of the Control Interface of a Robotic Arm by Non-experts

Abstract: Abstract. In this paper we study the relation between the performance of use and user preferences for a robotic arm control interface. We are interested in the user preference of non-experts after a one-shot evaluation of the interfaces on a test task. We also probe into the possible relation between user performance and individual factors. After a focus group study, we choose to compare the robotic arm joystick and a graphical user interface. Then, we studied the user performance and subjective evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This means they preferred to be in direct teleoperation mode, rather than sending high-level commands to the robot through the interface or supervising the robot's autonomous activity. This result is in line with another experimental study we conducted in the past on a teleoperation setup with the Kinova Jaco arm [20], where we found that participants preferred to use joysticks than graphical interfaces even if they made more errors with the hand-held devices. Among the motivation for this preference, the participants reported that they felt more in control, they felt they could improve their performance over time (expected improvement), had fewer attention switches and could focus exclusively on the visual feedback (looking at the robot).…”
Section: Joystickssupporting
confidence: 91%
See 1 more Smart Citation
“…This means they preferred to be in direct teleoperation mode, rather than sending high-level commands to the robot through the interface or supervising the robot's autonomous activity. This result is in line with another experimental study we conducted in the past on a teleoperation setup with the Kinova Jaco arm [20], where we found that participants preferred to use joysticks than graphical interfaces even if they made more errors with the hand-held devices. Among the motivation for this preference, the participants reported that they felt more in control, they felt they could improve their performance over time (expected improvement), had fewer attention switches and could focus exclusively on the visual feedback (looking at the robot).…”
Section: Joystickssupporting
confidence: 91%
“…The concept of identifying the key points, the sequence and the repetition of operations was not intuitive for the construction workers; other participants (robotics engineers) familiar with those questions understood the principle but had issues when using the interface to configure the operations. We encountered similar issues as in [20], which means more attention switches and cognitive operations for the graphical interface, even if it could enable the operator to automatically perform certain operations without error, such as automatically aligning the robot forks to the roof tile.…”
Section: Joysticksmentioning
confidence: 99%
“…The number of young patients with functional impairment of the upper limbs caused by stroke has increased rapidly, as influenced by accelerated pace of life, poor lifestyles and environmental factors [1,2]. Limb movement disorder, which is caused by hemiplegia after stroke, not only reduces the quality of life of patients, but also brings great pain to their physiology and psychology.…”
Section: Introductionmentioning
confidence: 99%